La munificenza episcopale al tramonto dell’Esarcato. Il segnacolo di Giovanni V nella basilica di Sant’Apollinare in Classe (a. 731) - Novara, Paola (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
Starting from the archbishop Giovanni Romano, the Ravenna prelates chose the extra-urban basilica of Sant'Apollinare in Classe as a burial place, and this continued until at least the ninth century. The tombs re-employed ancient sarcophagi and were placed in sight in the church’s courtyard, in imitation of the Vatican Paradisum. An illustration of the building before the great works done in the 18th century accurately describes the layout of the sarcophagi in the entrance space. Near each sarcophagus there was an inscription which indicated the name of the inhumed bishop. Currently only one part of those burial places survives, as well as a slab with the name of the archbishop that is placed on the left wall of the building, near the sarcophagus containing the remains of Giovanni V iuniore. The slab is dated to 731 and was placed to identify the location of the tomb, but at the same time it contains the reference to the donation of a fund made by the bishop to the monks residing in Sant'Apollinare. The table has not yet been studied in depth. This intervention will try to fill the gap.